A flexure hinged piezoelectric stick–slip actuator with high velocity and linearity for long-stroke nano-positioning. (1st July 2022) - Qiao, Guangda; Ning, Peng; Gao, Qi; Yu, Yang; Lu, Xiaohui; Yang, Shitong; Cheng, Tinghai
Abstract: It is difficult to simultaneously achieve high linearity, high velocity, and high resolution for long-stroke piezoelectric actuators due to their discontinuity. To improve the velocity and linearity, a linear piezoelectric stick–slip actuator is proposed inspired by the fast response characteristics of piezoelectrics, which can achieve dynamic adjustment of the normal pressure by the design of flexure hinge structure. Additionally, a new dynamic model of piezoelectric stick–slip is proposed, and the step characteristics of the backward motion to displacement surge are simulated by the proposed model. The dynamic adjustment of the normal pressure can be increased by adding the inertia block to the end of the driving arm. Compared with the performance of the actuator without an inertia block, the velocity is increased, the backward motion is suppressed, and the linearity is improved. Moreover, the linear fitting correlation coefficients R 2 of displacement curve is used to evaluate the linearity of the actuator, which can reach 0.9999 at both low (10 Hz) and high (1300 Hz) frequencies, the maximum velocity is 101.76 mm s −1, the stroke is 75 mm, and the resolution is 25 nm.